The Effect of Training and Non-Physical Work Environment on Performance Mediated by Work Motivation - Karuniawati, Santi Dwi Juli; Halim, Abdul; Farhan, Djuni (MEC-J (Management and Economics Journal), 2022)
This study examines the effect of training and non-physical environment on performance, either directly or mediated by work motivation. The research location is the APIP Regional Inspectorate of Malang City. Population and sample are all 44 APIP employees. The data is collected by five-point Likert scale. The collected data is analyzed by path analysis. The validity, reliability, and classical assumption tests were done before path analysis.Â  The study results prove the following points. First, training affects on work motivation. Second, non-physical environment affects on work motivation. Three, training effects performance. Fourth, non-physical environment affects on performance. Fifth, work motivations affects on performance. Sixth, training affects on performance through work motivation. Seventh, non-physical environment effects on performance through work motivation.